Effectiveness of Anthocyanins on Kidney Fibrosis; A Systemic Literature Review - Lusiana, Evi; Azizah, Aida Nur; Islami, Arya Putera (Faculty of Medicine, 2024)
Renal fibrosis refers to the abnormal accumulation of extracellular matrix during the process of tissue repair. Kidney fibrosis is mostly caused by chronic inflammation, which leads to tissue remodeling and subsequently impairs kidney function, resulting in a reduction in the glomerular filtration rate (GFR). Reduced glomerular filtration rate (GFR) can elevate blood concentrations of urea and creatinine. The chemicals known as anthocyanins possess anti-inflammatory and antioxidant characteristics, hence potentially enhancing renal function. This study was conducted based on a literature review approach, utilizing journal papers published over the past decade (2015-2024) obtained from Pubmed, Science Direct, and Google Scholar. This article aims to represent the diverse scientific investigations made on the efficacy of anthocyanins in enhancing renal function in cases with renal fibrosis. The present study indicates that anthocyanins have a positive impact on kidney function by effectively lowering urea and creatinine levels in individuals with renal fibrosis.